Passing for human : a graphic memoir - Finck, Liana (Random House, 2018)
"Passing for Human is what Finck calls 'a neurological coming-of-age story,' one in which, through her childhood, human connection proved elusive and her most enduring relationships were with plants and rocks and imaginary friends; in which her mother was an artist whose creative life had been stifled by an unhappy first marriage and a deeply sexist society that seemed expressly designed to snuff out creativity in women; in which her father was a doctor who struggled in secret with the guilt of having passed his own form of otherness on to his daughter; and in which, as an adult, Finck finally finds her shadow again--and, with it, her true self"--